ENHANCING COMMUNITY ENGAGEMENT IN ECOTOURISM: DEVELOPING A PARTICIPATORY AND COMMUNITY-CENTERED FRAMEWORK - Ichsan; Azhar; Munardi (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
Ecotourism can promote sustainable tourism by conserving nature and empowering local communities, but meaningful participation faces challenges like lack of trust, limited capacity, and uneven benefit distribution. This study develops a participatory, community-centered framework to enhance community engagement in ecotourism, identifying key factors such as social capital, participatory governance, equitable benefit-sharing, capacity building, and institutional support. The framework emphasizes culturally sensitive approaches, valuing local wisdom, and empowering communities as agents of change. Key components include power-sharing, meaningful dialogue, joint learning, and sustainable institutional mechanisms like multi-stakeholder partnerships, dialogue platforms, participatory monitoring systems, and equitable benefit-sharing. Recommendations for practitioners and policymakers focus on adopting bottom-up approaches, strengthening social capital, and developing inclusive institutional mechanisms. Further empirical research is needed to validate the framework and address the dynamics of specific community groups. This study advances understanding of community participation in ecotourism and offers practical guidance for inclusive, sustainable tourism development.